A CORRELATION BETWEEN PASSIVE VOICE MASTERY AND WRITING REPORT TEXT ABILITY (A STUDY AT THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 1 TUKKA IN 2018/2019 ACADEMIC YEAR) - hamdiah Safitri (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Abstract: This study aims to know whether there is a significant correlation between passive voice mastery and writing report text ability at the eleventh grade students of SMA Negeri 1 Tukka. The research was conducted by using descriptive method with 36 students as the sample and they were taken by using purposive sampling technique from 71 students. Test was used in collecting the data. Based on descriptive analysis, it could be found: a) The description of the students’ passive voice mastery at the eleventh grade students of SMA Negeri 1 Tukka is categorized “good”, it can be seen from the mean score of the students, that is 78. b)The description of the writing report text at the eleventh grade students of SMA Negeri 1 Tukka is categorized “good”, it can be seen from the mean score of the students, that is 79. c) The hypothesis in this research was accepted. It means that “There is a significant correlation of passive voice mastery and writing report text ability at the eleventh grade students of SMA Negeri 1 Tukka”. It can be seen from the rxy (0.626) is greater than the score of rtable (0.270) or 0.626 > 0.3291 at 5% level of significant.